Complex Rock Mechanics Problems and Risk Prevention Solutions - Chun Zhu; Ming Huang; Qiang Cai; Yujun Zuo; Shibin Tang; Qian Yin (Applied Sciences)
The emergence of rock mechanics was driven by the need to address stability issues in rock engineering and to examine conditions leading to rock failure [...]